Effectiveness of using representative training methodology for teaching physical education in universities and colleges - Shumova N.S.; Peng Jiaxin (Theory and Practice of Physical Culture, 2024)
Objective of the study was a comparative assessment of the effectiveness of the representative training technique and traditional methods of teaching Taijiquan. Methods and structure of the study. The scientific work was carried out in the athletics arena of the Sports Faculty of Soochow University. At the beginning of the study, the subjects (n=39, 17-25 years old, qualification – I-II category) were divided into experimental (EG, n=20, 10 girls, 10 boys) and control (CG, n=19, 9 girls, 10 boys) group. The EG included subjects who, in the opinion of the trainer, were less capable of successfully mastering the basic elements of Taijiquan, who showed the lowest activity in training and were in greater need of the help of a psychologist. Results and conclusions. In the experimental group, the quality of performing three Taijiquan exercises after a training cycle using the representative training technique significantly increased both according to self-assessment and as assessed by the trainer. In the control group, after a cycle of training conducted according to the usual university methodology, the quality of performing two of the three exercises, both according to self-assessment and as assessed by the trainer, on the contrary, significantly decreased; ratings and self-assessments of only the quality of performing the first exercise significantly increased (p<0.01), since its development was not so strongly influenced by the psychological fatigue of the subjects. Participants in the CG require volitional efforts to perform exercises, which leads to psychological fatigue.